Demosponges littorales des iles Kerkennah - BEN MUSTAPHA, Karim (INSTM Bulletin : Marine and Freshwater Sciences, 2007)
Demosponges from Kerkennah Islands were studied, mainly regarding their systematic position and were briefly compared to demosponges from Mediterranean infralittoral area. We collected 111 specimens from 11 different sites around Kerkennah islands, principally from Posidonia meadows, from 0,5 to 12 m depth, and we identified 50 species. Among them 19 were listed for the first time in Tunisia, while 2 were new for the Mediterranean, and 8 should be new species: Timea sp1 ; Timea sp2 ; Batzella sp ; Clathria (Microciona) sp1 ; Clathria (Microciona) sp2 ; Clathria sp ; Haliclona sp ; Sarcotragus fasciculatus var sp2. Finally, 7 species are endemic to the Mediterranean, while Ircinia chevreuxi seems to be endemic to the south of Tunisia